The Life Mission Theory III. Theory of Talent - Soren Ventegodt; Niels Jorgen Andersen; Joav Merrick (The Scientific World Journal)
When we acknowledge our purpose as the essence of our self, when we take all our power into use in an effortless way, and when we fully accept our own nature — including sex and sexuality, our purpose of life takes the form of a unique talent. Using this talent gives the experience of happiness. A person in his natural state of being uses his core talent in a conscious, joyful, and effortless way, contributing to the world the best he or she has to offer. Full expression of self happens when a person, in full acceptance of body and life, with whole-hearted intension, uses all his personal powers to realize his core talent and all associated talents, to contribute to his beloved and to the world. Thus, self-actualisation is a result of a person fully expressing and realizing his core talent.The theory of talent states that a core talent can be expressed optimally when a human being takes possession of a three-dimensional space with the axis of purpose, power and gender, as we have a threefold need: 1-Acknowledging our core talent (our purpose of life) and intending it 2-Understanding our potential powers and manifesting them 3-Accepting our human form including our sex and expressing itThe first dimension is spiritual, the next dimension is mental, emotional and physical, and the third dimension is bodily and sexual. We manifest our talents in a giving movement from the bottom of our soul trough our biological nature onto the subject and object of the outer world. These three dimensions can be drawn as three axes, one saggital axis called purpose or love or me-you, one vertical axis called power or consciousness (light) or heaven-earth, and one horizontal axis called gender or joy or male-female. The three core dimensions of human existence are considered of equal importance for expression of our life purpose, life mission, or core talent. Each of the dimensions is connected to special needs. When these needs are not fulfilled, we suffer and if this suffering becomes unbearable we deny the dimension or a part of is. This is why the dimensions of purpose, power and gender become suppressed from our consciousness.